Optimization of Boiling Time for Maximum Curcuminoid Yield in a Traditional Turmeric Tamarind Jamu Using UV-Vis Spectrophotometry: Optimasi Waktu Perebusan untuk Hasil Kurkuminoid Maksimum dalam Jamu Kunyit Asam Jawa Tradisional Menggunakan Spektrofotometri UV-Vis - aditya raharjo (Universitas Muhammadiyah Purwokerto, 2026)
Introduction: Turmeric tamarind herbal drink (Jamu Kunyit Asam) is a popular traditional medicine in Indonesia, valued for the health benefits of curcuminoids from turmeric. However, traditional preparation methods, particularly boiling time, are not standardized, potentially leading to inconsistent curcuminoid content, which affects efficacy. Objective: This study aimed to determine the effect of boiling time on the curcuminoid content in Jamu Kunyit Asam and to identify the optimal boiling time to achieve the maximum concentration. Methods: Fresh curcuma rhizomes (Curcuma longa L.) and tamarind fructus (Tamarindus indica L.) were boiled at 90 ± 2°C. Samples were collected at 5, 10, 15, 20, and 30-minute intervals. Curcuminoids were isolated using liquid-liquid extraction with chloroform and quantified using a validated UV-Vis spectrophotometry method at a maximum wavelength of 423 nm. Results: The analytical method was validated and showed excellent linearity (r = 0.9997), accuracy (92% recovery), and precision (%RSD = 0.89). The results demonstrated a non-linear relationship between boiling time and curcuminoid content. The concentration increased sharply to a peak of 57.602 ppm at the 10-minute mark, followed by a consistent decrease to 24.576 ppm by 30 minutes. Conclusion: The optimal boiling time for maximizing curcuminoid content in Jamu Kunyit Asam is 10 minutes at 90°C. Boiling for less than 10 minutes results in incomplete extraction, while boiling longer leads to significant thermal degradation of curcuminoids. This finding provides a scientific basis for standardizing the preparation of this traditional herbal medicine to ensure optimal bioactive compound content.